Assessment of physico-chemical parameters of rainbow trout farms for the evaluation of potential threat to natural streams in Nepal - Ghimire, Payaswini; Niraula, Archana; Rai, Anuradha; Pandey, Aastha; Gurung, Smriti; Sharma, Chhatra Mani (International Journal of Environment, 2017)
Three trout farms from Nepal were studied to investigate the changes in physico-chemical parameters and their potential threat to natural water bodies receiving the effluents. Reference and impact sites were determined in each farm so as to find out the level of impacts due to farming activities. Some of the parameters such as dissolved oxygen, turbidity, conductivity, and total dissolve solids were significantly changed in the impacted zones compared to reference sites. Similarly, concentrations of some major ions such as calcium and sodium were increased in the impacted zones. On the other hand, some of the parameters such as pH and potassium did not change in the impacted zone although their concentrations were different among farms studied. Nevertheless, the overall changes in the physico-chemical parameters did not pose health risk to the aquatic ecosystems receiving effluents from these fish farms as the concentrations were below the prescribed levels by Environmental Protection Agency (EPA) as well as Nepal Environment Statistics. This is an indication that, although fish farming activities are degrading water qualities, there is no threat to the water quality receiving the effluents yet probably due to small scale farming. The increase in number of fish farms in the same area, however might pose risk to the ecological health in the region which warrants regular monitoring. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-2, Mar-May 2017, Page: 43-55